Pengaruh Pemahaman Perencana Keuangan, Pengelola Keuangan, dan Implementasi PSAK 109 Terhadap Pelaporan Keuangan Pada Organisasi Zakat di Karesidenan Madiun - Amin Nurjanah; Ahmad Kudhori; Yopie Diondy Kurniawan (Jurnal Ekonomi, Akuntansi, dan Perpajakan, 2024)
The purpose of this study is to see how the understanding of financial planning, financial management, and the implementation of PSAK 109 impact the way zakat organizations in Madiun Karesidenan report their finances. This research is quantitative and uses multiple linear regression analysis. The research shows that the implementation of PSAK 109 does not affect the financial reporting of zakat organizations; instead, the understanding of financial planners and financial managers improves financial reporting. This shows that financial planners and financial managers still do a poor job in understanding and implementing Islamic financial accounting standards (PSAK 109). This study suggests that financial planners and financial managers should be trained and educated about PSAK 109. In addition, zakat organizations should be trained and assisted in the implementation of PSAK 109 to obtain accountable financial statements